2009
DOI: 10.1007/s10530-009-9616-z
|View full text |Cite
|
Sign up to set email alerts
|

The Indian brown mongoose, yet another invader in Fiji

Abstract: A thriving population of the Indian brown mongoose (Herpestes fuscus)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The result that the mongoose was the most common predator agrees with the findings of Patbandha et al [ 21 ] who reported the mongoose as the most important factor in the death of chickens in India. Although there are no similar studies on chickens in Fiji and nearby Island countries, the mongoose has been reported to be a huge challenge as an invasive species in Fiji [ 22 ]. It was unexpected that domestic dogs are considered problematic predators for indigenous chickens in Fiji, as they are not usually referred to as predators under scavenging systems [ 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result that the mongoose was the most common predator agrees with the findings of Patbandha et al [ 21 ] who reported the mongoose as the most important factor in the death of chickens in India. Although there are no similar studies on chickens in Fiji and nearby Island countries, the mongoose has been reported to be a huge challenge as an invasive species in Fiji [ 22 ]. It was unexpected that domestic dogs are considered problematic predators for indigenous chickens in Fiji, as they are not usually referred to as predators under scavenging systems [ 17 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finding that a small portion of the indigenous poultry owning households did not provide any housing for their chickens tallies with findings by Badubi et al [ 27 ] who reported that, in areas without predators that can climb trees, chickens roost on the treetops or any raised items at night. This, however, can be a challenge in Fiji considering that the mongoose, which is the main predator, can climb trees and any other elevated areas [ 22 ]. Extension services on housing practices for indigenous chicken producers are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…This mongoose is an agile predator; in addition to rats and snakes, it feeds on a variety of small mammals, reptiles, birds, invertebrates, and eggs (Veron et al 2009). For example, extinction of the barred-winged rail (Nesoclopeus poecilopterus) in Fiji coincided with introduction of the small Indian mongoose there (Gorman 1975, Simberloff and Rejmanek 2011), and Morley and Winder (2013) demonstrated that the mongoose was causal in the decline of at least three ground-dwelling birds: the Pacific black duck (Anas superciliosay, the banded rail (Gallirallus philippensisy, and the purple swamphen (Porphyrio porphyrio).…”
Section: Ecology Of the Small Indian Mongoosementioning
confidence: 99%